Preparation of metal-ion containing polymers: Synthesis and characterization of methacryliccopolymers containing copper ion. (23rd October 2015) - Gil, Manjae; Kim, Hyojin; Bae, Joonwon; Cha, Sang-Ho; Lee, Kyung Jin
Abstract: Organic-inorganic hybrid materials have attained great attention due to their complementary properties from each material. Although there have been numerous reports considering the hybrid materials, it is still challenging task to develop easy accessible and versatile method for fabrication of multifunctional organic-inorganic hybrid materials. Herein, we propose novel concept to prepare metal-ion containing polymeric materials. Copper containing copolymers were prepared via radical polymerization of the copper containing monomers with several different monomers. The copper nanoparticles obtained from the direct chemical reduction show the different oxidation and hydroxidation behaviors depending on the degree of interactions for the functional groups in copper containing polymers with oxygen and/or water. Finally, because these copper containing copolymers were shown to be soluble in various organic solvents, we have attempted to produce nanofibers using electrospinning in order to confirm the excellent processability of prepared copper containing polymer. Graphical abstract: